Enhanced Interior Gateway Routing Protocol (EIGRP) website based on cisco router 2811 using Application Programming Interface (API) from cisco - Sudaryanto Sudaryanto; Anggraini Kusumaningrum; Yuliani Indrianingsih; Dadan Rachman Prabowo (Compiler, 2021)
Enhanced Interior Gateway Routing Protocol (EIGRP) is a routing protocol that can be used to determine the path of data to be sent. EIGRP can achieve goals and study interconnected networks to obtain useful information to determine the best path. EIGRP is only adopted by Cisco routers or can be called a Cisco Proprietary Protocol, which can only be used on Cisco router devices. Currently, the EIGRP routing configuration uses the command line. For this reason, a Website-based EIGRP system was created and can be accessed remotely (remotely) with the aim of providing freedom of access and not focusing on one device. Website-based EIGRP system was created by utilizing Cisco's API as a liaison between the programming language and Cisco Router 2811 software. Telnet utilization plays a very important role in creating a Website-based EIGRP System where Telnet can provide wider access in management. By visiting the host and port of the router, the EIGRP Website Based System can easily do this. The results of the test in this study indicate that the Website-based EIGRP system is proven to be able to configure, so that administrators can use it for device management of Cisco Router 2811.